Executive functions in children with developmental language disorder: a systematic review and meta-analysis - Niu, Tengfei; Wang, Shiqiang; Ma, Jingxi; Zeng, Xiaoping; Xue, Ruiling (Frontiers in Neuroscience, 2024)
The purpose of the current study was to assess the differences between children with developmental language disorder (DLD) and typically developing (TD) children in their performance of executive functions from working memory, inhibitory control, and cognitive flexibility. Methods: We performed a systematical search of PubMed, Embase, Cochrane, and Web of Science for case control studies (published in English between January 1, 1950, and October 11, 2023) comparing the differences in the performance of executive functions between DLD and TD children. Results: Forty eligible studies were included in the present study (N=3168 participants). In comparison with TD children, DLD children exhibited significantly poorer performances in all six verbal working memory tasks (backward digit recall task, SMD -1.4321, 95% CI -2.2692 to -0.5950; listening recall task, SMD -1.4469, 95% CI -1.7737 to -1.1202; counting recall task, SMD -0.9192, 95% CI -1.4089 to -0.4295; digit recall task, SMD -1.2321, 95% CI -1.4397 to -1.0244; word list recall task, SMD -1.1375, 95% CI -1.5579 to -0.7171; nonword recall task, SMD -1.5355, 95% CI -1.8122 to -1.2589). However, regarding inhibitory control and cognitive flexibility, the differences between DLD and TD children depended on specific circumstances. In subgroup analyses of all verbal working memory tasks, DLD children presented notably lower performance than TD children in both the monolingual English and monolingual non-English groups, and in both the preschooler and school-aged groups. Conclusion: This study proves that verbal working memory deficits can be seen as a marker for children with DLD and are not affected by age or language type.